Frontispiece: Lights and Shadows of DMSO as Solvent for Tin Halide Perovskites. Issue 12 (24th February 2022) - Pascual, Jorge; Di Girolamo, Diego; Flatken, Marion A.; Aldamasy, Mahmoud H.; Li, Guixiang; Li, Meng; Abate, Antonio
Abstract : Current protocols for solution‐processed tin halide perovskite thin films rely on the use of DMSO. However, this solvent was recently found to oxidise tin species. This source of defects in the films may be the reason for the bottlenecks in device performance and reproducibility. DMSO‐free processes may avoid this problem, but lack a controlled crystallization so far. Understanding the chemistry of tin perovskites in new solvent systems would allow fabricating thin films of the highest quality.